2009
DOI: 10.1253/circj.cj-08-0370
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin, Leukocytosis and Clinical Outcomes of ST-Elevation Myocardial Infarction Treated With Primary Angioplasty Anin Myocardial Infarction Registry

Abstract: Background Hemoglobin (Hb) levels may interact with inflammatory activation, but it is unknown whether the interaction has any impact on clinical outcomes in acute coronary syndromes. The aim of this study was to assess the relationship between admission Hb levels, leukocytosis and clinical outcomes of ST-elevation myocardial infarction (STEMI) treated with primary angioplasty. Methods and ResultsThe study group comprised 1,904 (1,380 men) patients with STEMI treated with primary percutaneous coronary interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 23 publications
3
23
1
Order By: Relevance
“…Accordingly, our data indicate negative correlation between haemoglobin levels and increased blood leukocytes levels, which suggest increasing inflammatory process [17]. Elevated leukocytes may predict incident cardiovascular events.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Accordingly, our data indicate negative correlation between haemoglobin levels and increased blood leukocytes levels, which suggest increasing inflammatory process [17]. Elevated leukocytes may predict incident cardiovascular events.…”
Section: Discussionsupporting
confidence: 49%
“…It may influence the development of ACS some possible patho-physiological mechanisms including endothelial cell injury caused by proteolytic enzymes, vessel plugging, decreased perfusion, increased expression of monocyte tissue factors, activation of coagulation system, increased thrombus formation, and involvement in hematologic stress syndrome [18,19]. Among other links leukocytosis with ACS outcomes, it is hypothesized that elevated count of leukocytes may reflect a more severe condition or an association with other comorbidities that convey increased risk of adverse outcomes, such as infection, malignancy, trauma, and inflammation commonly linked to anaemia [17].…”
Section: Discussionmentioning
confidence: 99%
“…Complete blood cell (CBC) is a simple, easily and widely performed laboratory test. Among several CBC markers, the predictive value of white blood cell (WBC) and hemoglobin (Hb) for short- and long-term survival in patients with AMI has been relatively well established (3, 4, 5, 6, 7, 8), although some studies have refuted this association (9, 10, 11). …”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the risk markers for a specific cohort like ours may differ from: randomized studies due to selection bias, studies using different reperfusion strategies (including sole medical management), studies assessing different biomarkers or markers sampled after the reperfusion, studies of non-uniform conditions (including non-ST elevation acute coronary syndrome), studies employing composite (“softer”) endpoints, and finally, those assessing longer term follow-up, where disease progression and other late complications may override the markers of acute complications [1922]. Our cohort was the first previously showing the independent significance of leukocytosis and anemia in unselected patients treated with pPCI [5, 23, 24] and the detailed discussion regarding our independent risk markers in relation to other studies may be found elsewhere [5, 6, 23]. Given our methodology (blood sampling in patients within 0–12 h of STEMI onset and prior to the attempted reperfusion), it may be assumed that the baseline values of hematocrit and GFR closely represent their chronic levels and are not yet significantly affected by the course of the disease or its acute treatment.…”
Section: Discussionmentioning
confidence: 99%